background image

2.1. ORDER THEORY

30

2

.

a

t

(

b

\

a

) =

a

t

b

;

3

.

b

t

(

b

\

a

) =

b

;

4

. (

b

t

c

)

\

a

= (

b

\

a

)

t

(

c

\

a

).

Proof.

. We have

c

w

b

\

a

c

t

a

w

a

t

(

b

\

a

) =

a

t

b

w

b

;

c

t

a

w

b

c

=

c

t

(

c

\

a

)

w

(

a

\

a

)

t

(

c

\

a

) = (

a

t

c

)

\

a

w

b

\

a

.

So

c

w

b

\

a

c

t

a

w

b

that is

a

t −

is an upper adjoint of

− \

a

. By

a theorem above our lattice is co-brouwerian. By another theorem above

\

is a pseudodifference.

.

1

Obvious.

2

.

a

t

(

b

\

a

) =

a

t

l

z

A

b

v

a

t

z

=

l

a

t

z

z

A

, b

v

a

t

z

=

a

t

b.

3

.

b

t

(

b

\

a

) =

b

t

d

n

z

A

b

v

a

t

z

o

=

d

n

b

t

z

z

A

,b

v

a

t

z

o

=

b

.

4

Obviously (

b

t

c

)

\

a

w

b

\

a

and (

b

t

c

)

\

a

w

c

\

a

. Thus

(

b

t

c

)

\

a

w

(

b

\

a

)

t

(

c

\

a

). We have

(

b

\

a

)

t

(

c

\

a

)

t

a

=

((

b

\

a

)

t

a

)

t

((

c

\

a

)

t

a

) =

(

b

t

a

)

t

(

c

t

a

) =

a

t

b

t

c

w

b

t

c.

From this by definition of adjoints: (

b

\

a

)

t

(

c

\

a

)

w

(

b

t

c

)

\

a

.

Theorem

163

.

(

d

S

)

\

a

=

d

x

S

(

x

\

a

) for all

a

A

and

S

P

A

where

A

is a co-brouwerian lattice and

d

S

is defined.

Proof.

Because lower adjoint preserves all suprema.

Theorem

164

.

(

a

\

b

)

\

c

=

a

\

(

b

t

c

) for elements

a

,

b

,

c

of a co-frame.

Proof.

a

\

b

=

d

n

z

A

a

v

b

t

z

o

.

(

a

\

b

)

\

c

=

d

n

z

A

a

\

b

v

c

t

z

o

.

a

\

(

b

t

c

) =

d

n

z

A

a

v

b

t

c

t

z

o

.

It is left to prove

a

\

b

v

c

t

z

a

v

b

t

c

t

z

. But this follows from

corollary

155

.

Corollary

165

.

(((

a

0

\

a

1

)

\

. . .

)

\

a

n

) =

a

0

\

(

a

1

t · · · t

a

n

).

Proof.

By math induction.